Transgenerational effects of in ovo stimulation with synbiotic and choline on gonadal tissue across three generations - Mariam Ibrahim; Ewa Grochowska; Marek Bednarczyk; Katarzyna Stadnicka (Scientific Reports)
Abstract Epigenetic mechanisms play a pivotal role in hereditary processes, shaping phenotypic outcomes across generations. This study investigates the transgenerational impacts of in ovo injection of bioactive substances on gene expression and DNA methylation in the male gonads using the Green-legged Partridgelike chickens as a model organism. Synbiotic PoultryStar® (Biomin; PS) and choline were injected in ovo on the 12th day of egg incubation. In the F1 generation, three groups were established: (1) control (C, 0.9% physiological saline); (2) PS synbiotic (SYN, 2 mg/embryo); and (3) PS synbiotic combined with choline (SYNCH, 2 mg/embryo of synbiotic and 0.25 mg/embryo of choline). In subsequent F2 and F3 generations, groups SYN and SYNCH were further divided into two subgroups each: (A) only injected in F1 embryos (SYNs and SYNCHs); and (B) repeatedly injected in every generation (SYNr and SYNCHr). At 21 weeks post-hatching, gonadal tissues were sampled from F2 and F3 male chickens for transcriptomic and reduced representation bisulfite sequencing (RRBS). Synbiotic alone produced minimal and diminishing changes in gene expression across generations. In contrast, the single co-administration of synbiotic and choline in F1 embryos (SYNCHs) led to 1,897 differentially expressed genes (DEGs) and 786 differentially methylated regions (DMRs) in F3. Repeated administration across generations (SYNCHr) resulted in an even greater number of DEGs (2,804) and DMRs (2,880) in F3, reflecting a cumulative exposure effect. DEGs in SYNCH groups were mainly enriched in pathways related to cytoskeletal organization and extracellular matrix. In SYNCHs, methylation changes were associated with TGF-beta signaling, whereas SYNCHr showed additional enrichment in Wnt signaling, focal adhesion, and adipocytokine signaling pathways. Integrative analysis revealed coordinated changes in gene expression and DNA methylation, particularly in the F3 generation, identifying 37 genes (47 DMRs) in SYNCHs and 194 genes (306 DMRs) in SYNCHr. This study highlights the potential of prenatal epigenetic interventions to induce gene expression and DNA methylation changes across generations in reproductive tissues.